Safety and Appropriateness of Tourniquets in 105 Civilians. (1st November 2016) - Scerbo, Michelle H.; Mumm, Jacob P.; Gates, Keith; Love, Joseph D.; Wade, Charles E.; Holcomb, John B.; Cotton, Bryan A.
Abstract: Background: The United States military considers tourniquets to be effective for controlling bleeding from major limb trauma. The purpose of this study was to assess whether tourniquets are safely applied to the appropriate civilian patient with major limb trauma of any etiology.Methods: Following IRB approval, patients arriving to a level-1 trauma center between October 2008 and May 2013 with a prehospital (PH) or emergency department (ED) tourniquet were reviewed. Cases were assigned the following designations: absolute indication (operation within 2 hours for limb injury, vascular injury requiring repair/ligation, or traumatic amputation); relative indication (major musculoskeletal/soft-tissue injury requiring operation 2–8 hours after arrival, documented large blood loss); and non-indicated . Patients with absolute or relative indications for tourniquet placement were defined as indicated, while the remaining were designated as non-indicated. Complications potentially associated with tourniquets, including amputation, acute renal failure, compartment syndrome, nerve palsies, and venous thromboembolic events, were adjudicated by orthopedic, hand or trauma surgical staff. Univariate analysis was performed to compare patients with indicated versus non-indicated tourniquet placement.Results: A total of 105 patients received a tourniquet for injuries sustained via sharp objects, i.e., glass or knives (32%), motor vehicle collisions (30%), or other mechanisms (38%). A total of 94 patients (90%) had indicated tourniquet placement; 41 (44%) of which had a vascular injury. Demographics, mechanism, transport, and vitals were similar between patients that had indicated or non-indicated tourniquet placement. 48% of the indicated tourniquets placed PH were removed in the ED, compared to 100% of the non-indicated tourniquets (p < 0.01). The amputation rate was 32% among patients with indicated tourniquet placement (vs. 0%; p = 0.03). Acute renal failure (3.2 vs. 0%, p = 0.72), compartment syndrome (2.1 vs. 0%, p = 0.80), nerve palsies (5.3 vs. 0%; p = 0.57), and venous thromboembolic events (9.1 vs. 8.5%; p = 0.65) and were similar in patients that had indicated compared to non-indicated tourniquet placement. After adjudication, no complication was a result of tourniquet use.Conclusion: The current study suggests that PH and ED tourniquets are used safely and appropriately in civilians with major limb trauma that occur via blunt and penetrating mechanisms.